2004
DOI: 10.1091/mbc.e04-04-0296
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Dynamic Axes of Polarity Use Distinct Formin Isoforms in Budding Yeast

Abstract: Bud growth in yeast is guided by myosin-driven delivery of secretory vesicles from the mother cell to the bud. We find transport occurs along two sets of actin cables assembled by two formin isoforms. The Bnr1p formin assembles cables that radiate from the bud neck into the mother, providing a stable mother-bud axis. These cables also depend on septins at the neck and are required for efficient transport from the mother to the bud. The Bni1p formin assembles cables that line the bud cortex and target vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
208
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(229 citation statements)
references
References 106 publications
18
208
0
Order By: Relevance
“…It was shown that although depolymerization of all F-actin prevented polarization of most proteins at the bud tip, it did not prevent polarization of Cdc42 (Ayscough et al 1997;Irazoqui et al 2003). It was later shown that selective depolymerization of actin cables, but not actin patches, caused dispersal of Cdc42 from the bud tip (Irazoqui et al 2005;Pruyne et al 2004b). Actin patches are associated with sites of active endocytosis.…”
Section: Polarization Of Cdc42 By Membrane Traffic In Budding Yeastmentioning
confidence: 99%
“…It was shown that although depolymerization of all F-actin prevented polarization of most proteins at the bud tip, it did not prevent polarization of Cdc42 (Ayscough et al 1997;Irazoqui et al 2003). It was later shown that selective depolymerization of actin cables, but not actin patches, caused dispersal of Cdc42 from the bud tip (Irazoqui et al 2005;Pruyne et al 2004b). Actin patches are associated with sites of active endocytosis.…”
Section: Polarization Of Cdc42 By Membrane Traffic In Budding Yeastmentioning
confidence: 99%
“…Although S. pombe for3⌬ had no visible actin cables (Feierbach and Chang, 2001) or the cables were shorter in size and reduced in number (Nakano et al, 2002), cells were still able to grow in a polarized manner unlike a deletion of Agbni1. Different functions were also described for the baker's yeast formins ScBni1p and ScBnr1p (Pruyne et al, 2004). ScBni1p localizes mainly to the bud tip where it forms actin cables.…”
Section: Redundance Of Formins In a Gossypiimentioning
confidence: 99%
“…In S. cerevisiae, the two formins Bni1p and Bnr1p are required for cell polarity and cytokinesis with some overlapping and some different functions (Zahner et al, 1996;Evangelista et al, 1997;Imamura et al, 1997;Kamei et al, 1998;Pruyne et al, 2004). In Schizosaccharomyces pombe, three formins exist which are also involved in cell polarity and cytokinesis.…”
Section: Introductionmentioning
confidence: 99%
“…Little Bud6 is recovered in extracts of wild-type cells, so it would be very interesting to supplement the extracts with additional Bud6 protein and maybe thereby drive assembly in nonmitotic extracts. Another limitation is that no cable assembly was seen when the FH1-COOH region of Bnr1 was used, although this region can nucleate and elongate filaments, and cells expressing just Bnr1 have actin cables (19). To address these issues, it is likely that the method used for preparing the extract may need to be adjusted, perhaps increasing its concentration, or adding an ATP regenerating system, or "spiking" it with additional purified yeast actin.…”
mentioning
confidence: 99%